The distribution and heterogeneity of excitability in focal epileptic network potentially contribute to the seizure propagation - Fan, Denggui; Wu, Hongyu; Luan, Guoming; Wang, Qingyun (Frontiers in Psychiatry, 2023)
Different types of epileptic seizures involve different pathogenic regions and transmission modes. Existing dynamical models can explain the transmigration mechanisms involved in seizures but are limited to a single modality. Combining models with networks can reproduce scaled epileptic dynamics and is a beneficial approach to investigate the electrophysiological network mechanisms of epileptic seizures. We are now familiar with model state transitions but ignoring its evolution in the network. The structure and coupling interactions of the network, as well as the heterogeneity of both the node and network activities, may be among the influencing factors. In this article, we built a fully connected network with focal nodes prominently interacting and established a timescale separated epileptic network model. The factors affecting epileptic network seizure were explored by varying the connectivity patterns of focal network nodes and the modulating the distribution of network excitability. It is found that the whole brain network topology as the brain activity foundation affects the consistent delayed clustering seizure propagation. In addition, the network size and distribution heterogeneity of the focal excitatory nodes can influence seizure frequency. In particular, with the increasing of the network size and averaged excitability level of focal network, the seizure period decreases. In contrast, the larger heterogeneity of excitability for focal network nodes can lower the functional activity level (average degree) of focal network. There are also subtle effects of focal network topologies (connection patterns of excitatory nodes) that cannot be ignored along with non-focal nodes. We believe that unraveling the role of excitatory factors in seizure onset and propagation can be used to understand the dynamic mechanisms and neuromodulation of epilepsy, with profound implications for the treatment of epilepsy and even for the understanding of the brain.